STOP RASISME DAN TEGAKKAN KEADILAN DI KALANGAN MAHASISWA UNIVERSITAS INTERNASIONAL BATAM - Dame Afrina Sihombing; Hendi Sama; Teddy Jurnali; Rina Anggraini; Ayu Fauzia Rahmah; Andhika Bayu; Indah Lilian Sari Br Ambarita; Mujiyati Irsad; Ricky Kurniadi; Saffian Saffian; Sellinna Octaviani; Vina Liesty Indriani; Yulianti Yulianti (National Conference for Community Service Project (NaCosPro), 2020)
Racism is a belief that signifies the biological difference between the human race in cultural culture or individually, that a certain race is more dominant than other races. Racism can occur anywhere and can disturb someone so that the victim will feel inferior to their race. The training method used in this research is to make observations for examples of realization with data techniques using observation through the google form. The results of this study were carried out because there is often a process of racism that is deliberately carried out because the process of changing the environment of Batam International University students is then carried out through socialization through the Instagram social media platform, making clothes with writing to stop racism and making stickers and key chains.